Project-based learning in mathematics: A literatur review. (October 2020) - Fisher, D; Kusumah, Y S; Dahlan, J A
Abstract: This study is a literature study with a descriptive qualitative research with library research that attempts to describe project-based learning in mathematics learning. In this literature study research the author uses various written sources such as articles, journals and documents that are relevant to the study in this study. This study focuses on the characteristics of project-based learning, steps of project-based learning, and examples of project-based learning assessments, Differences in Project-Based Learning Emphasis and Traditional Learning, Examples of the application of project-based learning in mathematics. The next research that is interesting to be developed as research is project-based learning in increasing High Order Mathematical Thinking (HOTs).